2003
DOI: 10.1212/01.wnl.0000072323.19180.b7
|View full text |Cite
|
Sign up to set email alerts
|

Rostral lateral pontine infarction

Abstract: The authors correlated neurologic features of rostral lateral pontine infarct (rLPI) with lesion location on MRI. rLPI is a motor-sensory stroke presenting as crural monoparesis or crural dominant hemiparesis and segmental superficial or deep sensory disturbances. The dorsolateral pontine base causes crural paresis without supranuclear facial palsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 7 publications
2
17
0
Order By: Relevance
“…The statistical analysis of lesion location in these patients with motor hemiparesis as compared with the 111 patients in our study without paresis proved an area in the upper ventral to medial pons to be significantly associated with motor hemiparesis. This corresponds to earlier imaging studies on brainstem lesions causing corticospinal tract dysfunction 4, 8, 11. The corticospinal tract as depicted in the stereotactic atlas of Schaltenbrand and Wahren21 was affected by the lesion of every patient with motor hemiparesis (Fig 3).…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…The statistical analysis of lesion location in these patients with motor hemiparesis as compared with the 111 patients in our study without paresis proved an area in the upper ventral to medial pons to be significantly associated with motor hemiparesis. This corresponds to earlier imaging studies on brainstem lesions causing corticospinal tract dysfunction 4, 8, 11. The corticospinal tract as depicted in the stereotactic atlas of Schaltenbrand and Wahren21 was affected by the lesion of every patient with motor hemiparesis (Fig 3).…”
Section: Resultssupporting
confidence: 86%
“…Anatomical‐functional correlation studies are particularly difficult in the brainstem because of the close proximity of nuclei and fiber tracts. Lesion studies in experimental animals and a few human cases indicate a clear somatotopic order of the pyramidal tract in the internal capsule and at least in the upper brainstem, with fibers directed to the arm running more anteromedially and fibers directed to the leg more dorsolaterally 4, 9–11. Fibers of the arm and leg appear to overlap progressively within the lower brainstem 9, 10, 12.…”
mentioning
confidence: 98%
“…Regarding the feature of pontine infarction, it can be pointed out that the neurological symptoms are various depending on the distribution of the lesion 16. Actually, the neurological deficits were reported to be different between patients whose lesion was localized in the ventral part of pons and patients whose lesion was extended from ventral to dorsal part of pons 8. Recent reports mentioned that the ischemic lesion located in the lower pons showed a tendency of progressing stroke compared with the lesion located in the upper and middle pons 17,18.…”
Section: Discussionmentioning
confidence: 99%
“…the neurological deficits were reported to be different between patients whose lesion was localized in the ventral part of pons and patients whose lesion was extended from ventral to dorsal part of pons. 8 Recent reports mentioned that the ischemic lesion located in the lower pons showed a tendency of progressing stroke compared with the lesion located in the upper and middle pons. 17,18 Meanwhile, our data showed that there was no relation between worsening of symptoms and localization of ischemic lesion both in horizontally and vertically.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation